2013
DOI: 10.1371/journal.pone.0080317
|View full text |Cite
|
Sign up to set email alerts
|

Beclin 1 Deficiency Correlated with Lymph Node Metastasis, Predicts a Distinct Outcome in Intrahepatic and Extrahepatic Cholangiocarcinoma

Abstract: Autophagy can be tumor suppressive as well as promotive in regulation of tumorigenesis and disease progression. Accordingly, the prognostic significance of autophagy key regulator Beclin 1 was varied among different tumors. Here, we detected the clinicopathological and prognostic effect of Beclin 1 in the subtypes of intrahepatic cholangiocarcinoma (ICC) and extrahepatic cholangiocarcinoma (ECC). Beclin 1 expression level was detected by immunohistochemistry staining in 106 ICC and 74 ECC patients. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 43 publications
4
36
3
1
Order By: Relevance
“…However, in DHA‐treated CCA cells this effect is reinforced by the reduced expression of BCL‐2 and the higher expression of BECLIN1. It is to be noted that BECLIN1 was found expressed at very low level in metastatic and therapy‐resistant CCAs . The sustained hyper‐regulation of autophagy induced by DHA eventually precipitated CCA cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in DHA‐treated CCA cells this effect is reinforced by the reduced expression of BCL‐2 and the higher expression of BECLIN1. It is to be noted that BECLIN1 was found expressed at very low level in metastatic and therapy‐resistant CCAs . The sustained hyper‐regulation of autophagy induced by DHA eventually precipitated CCA cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, a lysosome‐mediated macromolecular degradation pathway, may exert a tumor suppressive function in CCA. In fact, low level of expression of the BECLIN1 autophagy protein was associated with metastatic CCAs and poor outcome in CCA patients …”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies reporting that beclin 1 expression is associated with chemosensitivity (27,28). Beclin 1 may affect the chemosensitivity of cancer cells through several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies addressing the expression of autophagy-related proteins in CC and its clinicopathological significance, such as for prognosis [17,18]; however, to the best of our knowledge, no study has dealt with the involvement of autophagy in premalignant lesions, BilIN and IPNB. Since the process of autophagy itself is completed within a short time, immunohistochemical granular expression of LC3 may indicate the accumulation of autophagic vacuoles due to induced and deregulated autophagy [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of autophagy in the process of cholangiocarcinogenesis via BilIN has not been studied, although several studies have reported the expression of autophagy-related proteins and its clinicopathological significance in CC [17,18]. We previously disclosed that cellular senescence participates in stepwise cholangiocarcinogenesis in the large bile duct (LBD) via BilIN [19]; that is, the expression of senescence-associated p16 INK4a occurs at an early stage, and then overexpression of EZH2 plays a role in the bypass/escape from senescence followed by the development of overt carcinoma [19].…”
Section: Introductionmentioning
confidence: 99%